If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+8x=2x-4
We move all terms to the left:
7+8x-(2x-4)=0
We get rid of parentheses
8x-2x+4+7=0
We add all the numbers together, and all the variables
6x+11=0
We move all terms containing x to the left, all other terms to the right
6x=-11
x=-11/6
x=-1+5/6
| 6(–5y−5)=–7−7(6y+17) | | 6=1/3x-4 | | 3x+2-1=-26 | | 4(16b+14)+8b=4(18b+14) | | 41+t=65 | | 8d+9=1 | | -7=4-1/3x | | 7p/10=5 | | w/14=–31 | | 7=-1/3x+4 | | 3.649+2.4v=146.329 | | w14=–31 | | 6h+3=-3 | | 7=4-1/3x | | -9x–12=15 | | 2(n+7)=-2(6n+7) | | 2.5=8.5-2x | | -4-8(1-3v)=-24 | | -19=4x-12 | | n+5=74 | | 78=n-15 | | 7-2g=-15 | | d-45=13 | | 22+x=76 | | 1.93(f-2)=9.65 | | 4a(3)-14=78 | | 3.25x-1.5=1.2513x-6y=10 | | -3-4x=-5 | | -7+11j=17+17j | | -10x3=30 | | -34+5x=-7(7+x)+7x | | 8a+1=-63 |